Student Engagement From Beyond the US: Increasing Resonance Through Reframing the Construct. Issue 4 (1st November 2020) - Trowler, Vicki; Schreiber, Birgit
Abstract: Student engagement offers many useful ways of thinking about student and institutional success. This article argues that more research and theorizing are required to make the construct relevant to living and learning communities, students, and institutions beyond the United States. Four pointers are discussed to expand and deepen the construct and to improve resonance across the world. The recommendations include moving beyond institution-centric forms of engagement and considering life-wide engagement, reviewing reductionistic indicators that rely on binaries of race and politics, and considering oppositional and challenging forms of being as a form of student engagement.